Pomegranate peel extract is an effective agent against MDR bacteria: Pomegranate peel extract against MDR bacteria - Alqahtani, Abdulaziz; Mohamed, Alzhraa Ali; Ahmad, Irfan; Alraey, Yasser; Asiri, Mohammed; Kopel, Jonathan; Alshahrani, Mohammed Merae (Cellular and Molecular Biology, 2023)
Multidrug-resistant (MDR) bacteria are one of the major public health threats facing humanity. Infections with MDR strains are difficult or impossible to treat with standard antibiotics leading to severe illnesses and even deaths. The spread of MDR bacteria has necessitated the search for alternative approaches that tackle MDR pathogens. Natural plants can be utilized as alternative therapeutic agents against the rise of MDR bacteria. In this study, we aimed to assess the antimicrobial activity of pomegranate peel extracts (PPE) against MDR clinical isolates. A total of 9 clinical isolates (8 MDR and 1 non-MDR clinical isolates) were collected and examined for their susceptibility to PPE. Using the zone of inhibition assay, 4 isolates (S. aureus, three MRSA isolates, Vancomycin-resistant Enterococci (VRE), and Acinetobacter baumannii) were sensitive to PPE. In Broth assay, 4 mg/ml PPE significantly reduced the growth (S. aureus, three MRSA isolates, Vancomycin-resistant Enterococci (VRE), and Acinetobacter baumannii), while 40 mg/ml PPE either significantly reduced or completely inhibited the growth of the isolates. The minimum bactericidal concentration (MBC) of PPE against S. aureus and MRSA-88 was 10 mg/ml. This study showed the potential of PPE as an alternative compound for treating infections caused by PPE-sensitive MDR bacteria.